Surfactant Regulation of the Solution-Mediated Phase Transformation of Nitrofurantoin Anhydrate to Monohydrate - Zhuangzhuang Chen; Xiyan Wang; An Chen; Lin Li; Zhongting Zhuang; Minshan Guo; Ting Cai (Pharmaceutical Research, 2026)

Corrigendum to “Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times” [Chem. Eng. J. 537 (2026) 176461] - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Bisphosphoglycerate mutase is involved in glucose metabolism and progression of nonalcoholic fatty liver disease based on liver organoids - Zheng Zhou; Xiyan Zheng; Xianqing Chen; Maoyun Xie; Fei Du; Zhiqun Lin; Xianjie Shi (Human Cell, 2026)

Projected changes in streamflow seasonality and flood characteristics in the Moskva R. Basin - Oxana Erina; Xiaohua Lin; Natalia Ogneva; Natalia Semenova; Dmitriy Sokolov; Georgy Ayzel; Xiyan Xu (Theoretical and Applied Climatology, 2026)

An experimental and numerical study of the auto-ignition characteristics of ammonia/propane blends - Hao Lin; Kai Zhang; Xiyan Jiang; Wenxue Gao; Xiaobei Cheng; Shijun Dong (Fuel, 2026)

Aconiti Lateralis Radix Praeparata active ingredients of Heishunpian potential on LPS-induced Nrf-2/NQO1/HO-1 and Smad3/Akt/p38 signalling pathways in chronic obstructive pulmonary disease: a network pharmacology study - Yingzhe Wang; Xiyan Niu; Jie Guo; Lin Jia; Qian Liu (Journal of Molecular Histology, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Polystyrene/polylactic acid microplastics impair transzonal projections and oocyte maturation via gut microbiota-mediated lipoprotein lipase inhibition - Jiacheng Zhang; Hangqi Hu; Yutian Zhu; Xiyan Xin; Yuxin Jin; Qiancheng Zhao; Haolin Zhang; Dai Heng; Ze Ma; Xicheng Chai; Ruifan Lin; Yue Zhao; et al. (Journal of Hazardous Materials, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Can Smart city policies enhance corporate environmental performance? Evidence from China - Hongwei Shao; Xuecong Tang; Xiyan Xiao; Yanna Ma; Ziqiang Lin (Environment, Development and Sustainability, 2024)

Transcriptome and metabolome profiling of interspecific CSSLs reveals general and specific mechanisms of drought resistance in cotton - Bei Han; Fengjiao Wang; Zhilin Liu; Lin Chen; Dandan Yue; Weinan Sun; Zhongxu Lin; Xianlong Zhang; Xiaofeng Zhou; Xiyan Yang (Theoretical and Applied Genetics, 2022)

Genome-wide analysis of CBL and CIPK family genes in cotton: conserved structures with divergent interactions and expression - Weinan Sun; Bing Zhang; Jinwu Deng; Lin Chen; Abid Ullah; Xiyan Yang (Physiology and Molecular Biology of Plants, 2021)

Genome-wide identification of MAPK cascade genes reveals the GhMAP3K14–GhMKK11–GhMPK31 pathway is involved in the drought response in cotton - Lin Chen; Heng Sun; Fengjiao Wang; Dandan Yue; Xiankun Shen; Weinan Sun; Xianlong Zhang; Xiyan Yang (Plant Molecular Biology, 2020)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)